Migration of Energetic Plasticizer in Advanced Energetic Composite Propellant Grains. Issue 2 (23rd November 2022) - Kumar, Amit; Chavan, Prakash V.; Bhatkhande, Dhananjay S.; Sadavarte, Vaibhav S.; Santosh Mada, S. S. N. M.; Pande, Shrikant M.
Abstract: Studies on the migration of nitrate ester plasticizers from advanced energetic nitrate ester plasticized polyester polyol (NEPE) propellants stored at 27o and 55 °C using HPLC showed that the nitrate ester content is depleting from the bulk of the propellant with time, upto 125 weeks, till equilibrium is reached. Diffussion coefficient for migration of nitrate ester estimated by Fick's 2nd law of diffusion reveals that the magnitude of estimated diffussion coefficient is high for the propellant sample stored at elevated temperature as compared to the samples stored at ambient condition, indicating the higher rate of plasticizer migration at high temperature. Also, the estimated diffussion coefficient for NG migration is higher than that for BTTN which is inline with its higher rate of migration. The diffussion coefficients have also been estimated by the tensile strength data of the stored propellants and its magnitude is marginally higher than the one estimated by the physical phenomenon of plasticizer migration as described by Fick's law. Hence it can be inferred that along with the post cure reaction, the plasticizer migration is also responsible for toughening of propellant during storage. Abstract :